Designing a therapeutic hepatitis B vaccine to circumvent immune tolerance. Issue 2 (1st February 2020) - Whitacre, DC; Peters, CJ; Sureau, C; Nio, K; Li, F; Su, L; Jones, JE; Isogawa, M; Sallberg, M; Frelin, L; Peterson, DL; Milich, DR
ABSTRACT: An effective prophylactic hepatitis B virus (HBV) vaccine has long been available but is ineffective for chronic infection. The primary cause of chronic hepatitis B (CHB) and greatest impediment for a therapeutic vaccine is the direct and indirect effects of immune tolerance to HBV antigens. The resulting defective CD4 + /CD8 + T cell response, poor cytokine production, insufficient neutralizing antibody (nAb) and poor response to HBsAg vaccination characterize CHB infection. The objective of this study was to develop virus-like-particles (VLPs) that elicit nAb to prevent viral spread and prime CD4 + /CD8 + T cells to eradicate intracellular HBV. Eight neutralizing B cell epitopes from the envelope PreS1 region were consolidated onto a species-variant of the HBV core protein, the woodchuck hepatitis core antigen (WHcAg). PreS1-specific B cell epitopes were chosen because of preferential expression on HBV virions. Because WHcAg and HBcAg are not crossreactive at the B cell level and only partially cross-reactive at the CD4 + /CD8 + T cell level, CD4 + T cells specific for WHcAg-unique T cell sites can provide cognate T-B cell help for anti-PreS1 Ab production that is not curtailed by immune tolerance. Immunization of immune tolerant HBV transgenic (Tg) mice with PreS1-WHc VLPs elicited levels of high titer anti-PreS1 nAbs equivalent to wildtype mice. Passive transfer of PreS1 nAbs into human-liver chimeric mice prevented acute infection and cleared serum HBV from mice previously infected with HBV in a model of CHB. At the T cell level, PreS1-WHc VLPs and hybrid WHcAg/HBcAg DNA immunogens elicited HBcAg-specific CD4 + Th and CD8 + CTL responses.